Being more certain about random assignment in social policy evaluations - Stafford, B. (Cambridge University Press, 2002)
Social experiments have been widely utilised in evaluations of social programmes in the US to identify ‘what works’, whilst in the UK their use is more controversial. This paper explores the paradigmatic, technical and practical issues evaluators confront in using randomised experiments to evaluate social policies. Possible remedies to some of these problems are outlined. It is argued that although no evaluation methodology is problem-free, policy makers and researchers should be more confident about the merits of using random assignment, provided it is used in conjunction with other methodologies more suited to understanding why and how interventions work.